REPUBLIC OF SPAIN – AN IMPOSSIBLE MISSION? - Petrović, Rajko Č (Political Review, 2023)
The subject of this research is the analysis of the history of Spanish republican thought, the implementation of the concept of the Republic of Spain in practice, and the contemporary views of the Spanish political and social public on this issue. The goal of the research is not only to describe the different phases of Spanish republicanism in the form of the First and Second Spanish Republics and their representatives but also to try to answer the question of whether in the foreseeable future, it is possible to expect the transformation of Spain from a monarchy to a republic for the third time in its history. Our initial hypothesis was that historical experience has shown that republican Spain is an "impossible mission" due to its strong royalist and Roman Catholic spirit. The results of the research point to the still significant position of the monarchy within the Spanish political system, to the small chances that the "Third Spanish Republic" will be proclaimed in the near future, but also to the fact that the debate about the form of government in Spain is still very much alive and that as such has an impact on political events in that country. During the research, we have used the historical method and the method of comparative analysis.
Keywords: First Spanish Republic, Second Spanish Republic, Roman Catholic Church, parliamentary monarchy